A Comunicação Não-Verbal: especial relevância à função espaço-território da (comunicação) proxémica" - Ribeiro, Ana Rita (2016)
Aristotle said "Man is a social animal," that does not know how to live isolated and need interaction with their peers. Over several millenniums the man was found many ways to communicate – from smoke signals to sign language or even writing – and this need not slowed down over the years, instead of this, became increasingly glaring. Communication has become increasingly imperative in our lives. But the communication has long ceased to be seen merely as a transmission of words. Nowadays, in the today's society, the man relates to others through two levels: verbal and non-verbal. These two dimensions of communication arise often together, completing or in opposition to, even if the human being does not realize it. Proxemics, as one of the areas covered in Non-Verbal Communication is responsible for studying the distances and proximities that are between people and spaces and how each of us do to protect and defend their personal territory. Will be the Gender, Age, Profession or the Barriers to Communication able to significantly influence the proxemic? The present study will answer to these questions.